2018
DOI: 10.18517/ijaseit.8.5.3929
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Technology in Education to Enhance Technical MOOCs

Abstract: The low completion rate issue in MOOCs has become one of the main highlights by researchers. It is reported that only 10 to 15 percent of the students were able to complete the MOOCs. This low completion rate is due to the students are less engaged with the MOOCs content causing them to become demotivated to complete the whole MOOCs. Engaging students in MOOCs environment, especially for non-technical subjects, suited very well. However, for technical MOOCs, it involves significant challenges because technical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Self-monitoring activities like weekly quizzes and assignments help learners to monitor their learning. This finding is consistent with Fesol et al (2018), who found that monitoring learning and active learning are among the elements of MOOC instructional design that contribute to students' positive perceptions. According to Belousova et al (2019), it is argued that an effective distance learning system should include mechanisms for students to self-monitor their educational progress.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Self-monitoring activities like weekly quizzes and assignments help learners to monitor their learning. This finding is consistent with Fesol et al (2018), who found that monitoring learning and active learning are among the elements of MOOC instructional design that contribute to students' positive perceptions. According to Belousova et al (2019), it is argued that an effective distance learning system should include mechanisms for students to self-monitor their educational progress.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the instructional design of MOOCs should be tailored to promote the acquisition of knowledge that can be easily applied in real-world scenarios. Fesol et al (2018) found that meaningful connection in the MOOC leads to a positive perception of the students. Monitoring learning is found to be another element of MOOC instructional design that is significantly related to intended perception.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Model for applying divest integrated technology in education. (Fesol et al, 2018) The success of remote education relies on various factors, and simply introducing online learning platforms is not enough. Current studies like (Nambiar, 2020;Elhaty et al, 2020;Al-Taweel et al, 2020;Stecuła & Wolniak, 2022) also emphasized challenges with regards to teaching and learning practical subjects using online platform.…”
Section: Literature Review Challenges Of Practical Subjects In Online...mentioning
confidence: 99%
“…Therefore, the solution of one size fits all can be difficult to meet the learners' needs and expectations [5]. Also, it is highlighted in [6] that the low completion rate is considered as an important issue that get researchers' interest. This low rate is because of the students are less engaged with the learning materials of the provided MOOCs.…”
Section: Introductionmentioning
confidence: 99%